Dynamic models of wind farms for power system studies: status by IEA Wind R&D Annex 21 - Tande, John O. (2013)
Dynamic models of wind farms for power system studies are at present not a standard feature of many software tools, but are being developed by research institutes, universities and commercial entities. Accurate dynamic wind farm models are critical; hence model validation is a key issue and taken up by IEA Wind R&D Annex 21. This international working group includes participants from nine countries, and has since start-up in 2002 developed a systematic approach for model benchmark testing. This paper present this methodology, including example benchmark test results, but also gives an overview of the various wind farm models now being available from both Annex partners and external entities.